Influence of reflux ratio on the anaerobic digestion of pig manure in leach beds coupled with continuous stirred tank reactors. (September 2019) - Yang, Jie; Wang, Dehan; Luo, Zifeng; Zeng, Weishen
Graphical abstract: Highlights: Mono-anaerobic digestion of pig manure in leach bed reactors is performed. Biogas slurry inoculation occurs during the pig manure digestion in a leach bed. Reflux significantly improves the efficiency of manure anaerobic digestion. Inorganic filtration medium is used for the mono-anaerobic digestion of pig manure. The emission of odour and yield of biogas slurry are significantly reduced. Abstract: The effect of reflux ratio on the anaerobic mono-digestion of pig manure (PM) in leach beds coupled with continuous stirred tank reactors (CSTRs) has been studied in this work, and contents of volatile fatty acids (VFAs) and biogas yields were determined for three groups of leach bed reactor (LBR) – CSTR systems. The obtained results indicated that the reflux of biogas slurry increased both the pH of the acid-producing phase and acetic acid yield and repeatedly degraded the refractory organic matter in the biogas slurry. The larger reflux ratio increased the inoculation volume and substantially enhanced the mass transfer process. The maximum values of the biogas and methane yields equal to 259.49 and 167.44 mL/g volatile solids, respectively, were achieved at a reflux ratio of 100%. Moreover, the weight of the PM leachate residue was reduced by 94.14%, and the total nutrient content (N + P2 O5  + K2 O) was relatively high (1.48%), which was suitable for vegetable seedling substrates. In conclusion, during the treatment of PM in LBR–CSTRs, the solid phase remains on the leach bed, and the leachate is supplied to a biogas tank, which effectively increases its stability of operation.